TRAINING FOR THE MANUFACTURE OF FROZEN FOOD PRODUCTS TO INCREASE COMMUNITY INCOME IN DEALING WITH THE IMPACT OF COVID-19 IN KONAWE UTARA DISTRICT - Muh. Yani Balaka; Asrip Putera; Nur Azisah; Isalman Isalman (Yayasan Education and Social Center, 2022)
The Covid-19 pandemic has had a negative impact on the joints of the community's economy, people's income has decreased due to limited economic activity in the community. Many people have lost their jobs, decreased income and growing unemployment. One solution that can be done is to develop a home industry, namely the manufacture of frozen food and market it online. With this activity it is hoped that it can increase people's income by only working at home, of course it can help the government in maintaining stability, especially the community's economy and also assist the government in reducing the spread of Covid-19 by keeping a distance or reducing gatherings in crowded places due to activities carried out at home. The implementation of this PkM activity focuses on two things, the first is related to training in producing ready-to-eat frozen food products, and the second is providing training on how to market frozen food products through effective online marketing channels. PkM activities will be attended by 30 housewives in North Konawe Regency